Improving The Creativity of Vocational School Teachers Through The Development of Artificial Intelligence-Based Educational Media - Armin Arif; Risqah Amaliah Kasman; Muhammad Fuad; Muhammad Fadli; Ian Muhammad Bintang P (ITEKES Permata Ilmu Maros, 2025)
The advancement of Artificial Intelligence (AI) technology has driven significant transformation in global education, requiring teachers not only to serve as instructors but also as innovators in educational media. However, vocational high school (SMK) teachers in Indonesia still face challenges in effectively integrating AI into the learning process. This community service program aimed to enhance the creativity of SMK teachers in developing AI-based educational media through integrated training and intensive mentoring. The activity was conducted collaboratively at SMK Negeri 2 Barru, consisting of a needs assessment, a one-day offline training, and a two-week hybrid mentoring phase. The training covered the use of AI platforms such as ChatGPT, Canva AI, Gamma App, and MagicSchool AI, along with strategies for designing creative media and implementing differentiated, project-based learning. The results showed a significant increase in participants’ understanding, with average test scores rising from 52 to 84. A total of 18 out of 40 teachers successfully produced innovative educational media, including infographics, animated videos, AI-based quizzes, and vocational practice simulations. Evaluation results indicated that 95% of participants found the program relevant, and 90% were highly satisfied. Some teachers had already implemented the AI-based media in their classrooms with positive student responses. This program demonstrated that systematic and contextual support can significantly enhance both pedagogical and technological competencies of vocational teachers. The findings highlight the strong potential of AI integration in vocational education when accompanied by sustainable mentoring. This program contributes to teacher capacity building and supports a more creative, adaptive, and future-ready digital education transformation.